Symptomatic care of late-onset Alexander disease presenting with area postrema-like syndrome with prednisolone; a case report - Safoura Zardadi; Ehsan Razmara; Maryam Rasoulinezhad; Meisam Babaei; Mohammad Reza Ashrafi; Neda Pak; Masoud Garshasbi; Ali Reza Tavasoli (BMC, 2022)
Abstract Background Alexander disease (AxD) is classified into AxD type I (infantile) and AxD type II (juvenile and adult form). We aimed to determine the potential genetic cause(s) contributing to the AxD type II manifestations in a 9-year-old male who presented area postrema-like syndrome and his vomiting and weight loss improved after taking prednisolone. Case presentation A normal cognitive 9-year-old boy with persistent nausea, vomiting, and a significant weight loss at the age of 6 years was noticed. He also experienced an episode of status epilepticus with generalized atonic seizures. He showed non-febrile infrequent multifocal motor seizures at the age of 40 days which were treated with phenobarbital. He exhibited normal physical growth and neurologic developmental milestones by the age of six. Occasionally vomiting unrelated to feeding was reported. Upon examination at 9 years, a weak gag reflex, prominent drooling, exaggerated knee-deep tendon reflexes (3+), and nasal tone speech was detected. All gastroenterological, biochemical, and metabolic assessments were normal. Brain magnetic resonance imaging (MRI) revealed bifrontal confluent deep and periventricular white matter signal changes, fine symmetric frontal white matter and bilateral caudate nucleus involvements with garland changes, and a hyperintense tumefactive-like lesion in the brain stem around the floor of the fourth ventricle and area postrema with contrast uptake in post-contrast T1-W images. Latter MRI at the age of 8 years showed enlarged area postrema lesion and bilateral middle cerebellar peduncles and dentate nuclei involvements. Due to clinical and genetic heterogeneities, whole-exome sequencing was performed and the candidate variant was confirmed by Sanger sequencing. A de novo heterozygous mutation, NM_001242376.1:c.262 C > T;R88C in exon 1 of the GFAP (OMIM: 137,780) was verified. Because of persistent vomiting and weight loss of 6.0 kg, prednisolone was prescribed which brought about ceasing vomiting and led to weight gaining of 3.0 kg over the next 3 months after treatment. Occasional attempts to discontinue prednisolone had been resulting in the reappearance of vomiting. Conclusions This study broadens the spectrum of symptomatic treatment in leukodystrophies and also shows that R88C mutation may lead to a broad range of phenotypes in AxD type II patients.